Trilhando pelos solos: uma trajetória de 11 anos - Anjos, Felipe Kenji dos [UNESP]; Moraes, Ana Paula da Silva [UNESP]; Nishizima, Mariana Lopes [UNESP]; Nunes, João Osvaldo Rodrigues [UNESP]; Veríssimo, Victor Emmanuel Albertin [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The research project and the University extension " Treading the soils" had its origin in 2004 , it is developed in the Soil Laboratory of FCT / UNESP (LabSoils), at the Campus of Presidente Prudente. The main purpose of this project is to approach the University and society through the study of the natural resource soil, including its formation, use and occupation as well the importance of their maintenance and conservation for humanity.

O projeto de pesquisa e extensão universitária “Trilhando pelos Solos” teve sua origem no ano de 2004, é desenvolvido no Laboratório de Solos da FCT/ UNESP (LabSolos), campus de Presidente Prudente. O objetivo principal do projeto é aproximar a universidade da sociedade, através do estudo do recurso natural solos, compreendendo sua formação, seu uso e ocupação e a importância da sua manutenção e conservação para a humanidade.
Keywords: Environment; Extension; Soils; Meio ambiente; Extensão; Solos